2013
DOI: 10.1149/05037.0031ecst
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Assisted Chemical Etching of Silicon Using Oxygen as an Oxidizing Agent: Influence of HF Concentration on Etching Rate and Pore Morphology

Abstract: Metal-assisted chemical etching of silicon is an electroless method that can produce porous silicon by immersing metal-modified silicon in a HF solution without electrical bias. We have been studying this etching using dissolved oxygen as an oxidizing agent and recently reported that the catalytic activity of noble metal particles including silver, gold, platinum, and rhodium, influences the cathodic reduction of oxygen and controls the etching rate. In this paper, we investigate the influence of the HF concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Lianto et al47 performed the etching with patterned Au strips and demonstrated that the pit formation became signicant with increasing the H 2 O 2 concentration. We observed the pore widening with Rh and Pt particles in HF-O 2 systems at low HF concentrations 41. Recently, Akan et al15 demonstrated, for the fabrication of X-ray zone plates, that the surface roughness became signicant and the etching depth under Au catalysts became smaller when the H 2 O 2 concentration is high.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…Lianto et al47 performed the etching with patterned Au strips and demonstrated that the pit formation became signicant with increasing the H 2 O 2 concentration. We observed the pore widening with Rh and Pt particles in HF-O 2 systems at low HF concentrations 41. Recently, Akan et al15 demonstrated, for the fabrication of X-ray zone plates, that the surface roughness became signicant and the etching depth under Au catalysts became smaller when the H 2 O 2 concentration is high.…”
mentioning
confidence: 54%
“…Formation of mesoporous Si by the metal-assisted etching has been known so far [1][2][3][4][5]7,28,31,32,34,37,40,45,46 as well as pore widening 36,39,41 and pit formation at the location away from the catalysts. 47,48 Such phenomena have been usually observed when using the catalysts with a high catalytic activity for the reduction of oxidizing agents.…”
Section: Formation Of Mesoporous Layermentioning
confidence: 99%
See 2 more Smart Citations
“…Metal catalyst plays an essential role for determining the etching behavior. 18,[28][29][30][31][32][33][34][35][36] Recently, Tamarov et al 36 comprehensively studied the etching behavior using various kinds…”
Section: Introductionmentioning
confidence: 99%